A comprehensive assessment of the transcriptome of cork oak (Quercus suber) through EST sequencing. - Pereira-Leal, José B; Abreu, Isabel a; Alabaça, Cláudia S; Almeida, Maria Helena; Almeida, Paulo; Almeida, Tânia; Amorim, Maria Isabel; Araújo, Susana; Azevedo, Herlânder; Badia, Aleix; Batista, Dora; Bohn, Andreas; et al. (BMC genomics, 2014)
BACKGROUND: Cork oak (Quercus suber) is one of the rare trees with the ability to produce cork, a material widely used to make wine bottle stoppers, flooring and insulation materials, among many other uses. The molecular mechanisms of cork formation are still poorly understood, in great part due to the difficulty in studying a species with a long life-cycle and for which there is scarce molecular/genomic information. Cork oak forests are of great ecological importance and represent a major economic and social resource in Southern Europe and Northern Africa. However, global warming is threatening the cork oak forests by imposing thermal, hydric and many types of novel biotic stresses. Despite the economic and social value of the Q. suber species, few genomic resources have been developed, useful for biotechnological applications and improved forest management. RESULTS: We generated in excess of 7 million sequence reads, by pyrosequencing 21 normalized cDNA libraries derived from multiple Q. suber tissues and organs, developmental stages and physiological conditions. We deployed a stringent sequence processing and assembly pipeline that resulted in the identification of ~159,000 unigenes. These were annotated according to their similarity to known plant genes, to known Interpro domains, GO classes and E.C. numbers. The phylogenetic extent of this ESTs set was investigated, and we found that cork oak revealed a significant new gene space that is not covered by other model species or EST sequencing projects. The raw data, as well as the full annotated assembly, are now available to the community in a dedicated web portal at http://www.corkoakdb.org. CONCLUSIONS: This genomic resource represents the first trancriptome study in a cork producing species. It can be explored to develop new tools and approaches to understand stress responses and developmental processes in forest trees, as well as the molecular cascades underlying cork differentiation and disease response.
APS
Keywords: Cork oak; EST sequencing; Quercus suber; transcriptome

Molecular Organization of the 25S-18S rDNA IGS of Fagus sylvatica and Quercus suber: A Comparative Analysis. - Inácio, Vera; Rocheta, Margarida; Morais-Cecílio, Leonor (PloS one, 2014)
The 35S ribosomal DNA (rDNA) units, repeated in tandem at one or more chromosomal loci, are separated by an intergenic spacer (IGS) containing functional elements involved in the regulation of transcription of downstream rRNA genes. In the present work, we have compared the IGS molecular organizations in two divergent species of Fagaceae, Fagus sylvatica and Quercus suber, aiming to comprehend the evolution of the IGS sequences within the family. Self- and cross-hybridization FISH was done on representative species of the Fagaceae. The IGS length variability and the methylation level of 18 and 25S rRNA genes were assessed in representatives of three genera of this family: Fagus, Quercus and Castanea. The intergenic spacers in Beech and Cork Oak showed similar overall organizations comprising putative functional elements needed for rRNA gene activity and containing a non-transcribed spacer (NTS), a promoter region, and a 5'-external transcribed spacer. In the NTS: the sub-repeats structure in Beech is more organized than in Cork Oak, sharing some short motifs which results in the lowest sequence similarity of the entire IGS; the AT-rich region differed in both spacers by a GC-rich block inserted in Cork Oak. The 5'-ETS is the region with the higher similarity, having nonetheless different lengths. FISH with the NTS-5'-ETS revealed fainter signals in cross-hybridization in agreement with the divergence between genera. The diversity of IGS lengths revealed variants from ∼2 kb in Fagus, and Quercus up to 5.3 kb in Castanea, and a lack of correlation between the number of variants and the number of rDNA loci in several species. Methylation of 25S Bam HI site was confirmed in all species and detected for the first time in the 18S of Q. suber and Q. faginea. These results provide important clues for the evolutionary trends of the rDNA 25S-18S IGS in the Fagaceae family.
APS
Keywords: chromosomal loci; Fagaceae; Fagus sylvatica; intergenic spacer; Quercus suber; ribosomal DNA

Expression of DNA methyltransferases is involved in Quercus suber cork quality - Ramos, Miguel; Rocheta, Margarida; Carvalho, Luísa; Inácio, Vera; Graça, José; Morais-Cecílio, Leonor (Tree Genetics & Genomes, 2013)
Abstract Cork oak (Quercus suber ) is an important Portuguese species, mainly due to the economic value of the cork it produces. Cork results from phellogen, a meristematic tissue, which can locally produce lenticels or have discontinu- ities, originating “defects”: pores and nail inclusions that are detrimental to cork industrial use. Epigenetic processes control plant development and its deregulation can lead to altered phenotypes; therefore, the study of epigenetic players in the phellogen is important to understand the emergence of cork's defects. DNA methyltransferases (DNMTs) and one protein associated to MET1 (DMAP1) were characterized in Q. suber, and their gene expression was analyzed in phellogen and con- tiguous differentiating cell layers of trees producing high and low quality cork, after the evaluation of their defects by physical and image analysis methods. All classes of DNMTs (MET, DRM, and CMT) with the respective canonical motifs were identified in Q. suber. The expression analyses of these genes showed that QsDRM2 was the most active methyltransferases in the cells analyzed, and that all the genes were differentially expressed in trees with distinct cork quality,with a tendency for higher expression levels in lowquality producers. Interestingly, the global methylation level was higher in cells with low expression of DNA methyltransferases. A positive and significant correlation was obtained between QsDMAP1 gene expression and the percentage of cork defects. This work provides the first evidence that cork quality in Q. suber is likely influenced by epigenetic mechanisms
Keywords: CMT3; Cork oak; Cork quality; DMAP1; DRM; MET1; MET2; phellogen activity

Corky, a gypsy-like retrotransposon is differentially transcribed in Quercus suber tissues. - Rocheta, Margarida; Carvalho, Luísa; Viegas, Wanda; Morais-Cecílio, Leonor (BMC research notes, 2012)
Background: Transposable elements (TEs) make up a large part of eukaryotic genomes. Due to their repetitive nature and to the fact that they harbour regulatory signals, TEs can be responsible for chromosomal rearrangements, movement of gene sequences and evolution of gene regulation and function. Retrotransposon ubiquity raises the question about their function in genomes and most are transcriptionally inactive due to rearrangements that compromise their activity. However, the activity of TEs is currently considered to have been one of the major processes in genome evolution. Findings: We report on the characterization of a transcriptionally active gypsy-like retrotransposon (named Corky) from Quercus suber, in a comparative and quantitative study of expression levels in different tissues and distinct developmental stages through RT-qPCR. We observed Corky’s differential transcription levels in all the tissues analysed. Conclusions: These results document that Corky’s transcription levels are not constant. Nevertheless, they depend upon the developmental stage, the tissue analysed and the potential occurring events during an individuals’ life span. This modulation brought upon by different developmental and environmental influences suggests an involvement of Corky in stress response and during development.
Keywords: corky; expression; ltr retroelement; Quercus suber; rt-qpcr

Genomic organization and dynamics of repetitive DNA sequences in representatives of three Fagaceae genera - Alves, Sofia; Ribeiro, Teresa; Inácio, Vera; Rocheta, Margarida; Morais-Cecílio, Leonor (Genome, 2012)
Oaks, chestnuts, and beeches are economically important species of the Fagaceae. To understand the relationship between these members of this family, a deep knowledge of their genome composition and organization is needed. In this work, we have isolated and characterized several AFLP fragments obtained from Quercus rotundifolia Lam. through homology searches in available databases. Genomic polymorphisms involving some of these sequences were evaluated in two species of Quercus, one of Castanea, and one of Fagus with specific primers. Comparative FISH analysis with generated sequences was performed in interphase nuclei of the four species, and the co-immunolocalization of 5-methylcytosine was also studied. Some of the sequences isolated proved to be genus-specific, while others were present in all the genera. Retroelements, either gypsy-like of the Tat/Athila clade or copia-like, are well represented, and most are dispersed in euchromatic regions of these species with no DNA methylation associated, pointing to an interspersed arrangement of these retroelements with potential gene-rich regions. A particular gypsy-sequence is dispersed in oaks and chestnut nuclei, but its confinement to chromocenters in beech evidences genome restructuring events during evolution of Fagaceae. Several sequences generated in this study proved to be good tools to comparatively study Fagaceae genome organization.
doi: 10.1139/g2012-020doi: 10.1139/g2012-020The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: AFLP; Castanea; euchromatin; Fagaceae; Fagus; Quercus; retroelements